2019
DOI: 10.3390/polym11050760
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Strong Parts from Poly (Lactic Acid) with a Desktop 3D Printer: A Case with Interrupted Shell

Abstract: The ability to form closed cavities inside the part printed is an important feature of Fused Filament Fabrication technology. A typical part consists of a dense shell bearing the primary load, filled with low-density plastic scaffold (infill). Such a constitution of the part provides in most cases appropriate strength and low weight. However, if the printed part shape includes horizontal (orthogonal to printer’s Z axis) flat surfaces other than its top and bottom surface, then the shell of the part becomes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Current study is the continuation of [61], which demonstrated the importance of part shape design with respect to FFF technology peculiarities and its influence on the sample strength.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Current study is the continuation of [61], which demonstrated the importance of part shape design with respect to FFF technology peculiarities and its influence on the sample strength.…”
Section: Introductionmentioning
confidence: 93%
“…The shapes of samples tested were inherited from previous study [61]. An item consisting of two connected coaxial cylinders of large (boss) and small (shaft) diameters was used as basic shape (Shape 1), it's dimensions and constitution (superposition of shell, bases and infill) of the printed part are shown on Figure 2.…”
Section: Sample Shapesmentioning
confidence: 99%
See 3 more Smart Citations